“Relación entre los factores de riesgo biodemográficos y el aborto en adolescentes en el hospital regional del Amazonas – Loreto” - Rodríguez Aspajo, Gladys Sofia (1994)
What is the relationship between biodemogref physical risk factors and abortion in adolescents Hospital Regional of the Amazon - Loreto? He aborted is a serious problem in l <: pob 1 t <: 1 c